Prophetic Ijtihad and Adaptive Legal Reasoning in Early Islamic Law - M. Findo Riatama; Siti Nurjanah; Siti Zumrotus Saadah (Journal of Social Science and Humanities, 2026)
This article examines Prophetic ijtihad as a foundational model of adaptive legal reasoning in early Islamic law. The problem addressed is the tendency to reduce Prophetic-era law to static textual authority while overlooking the interaction between revelation, reasoning, context, and consultation. Using qualitative library research with a historical-normative and conceptual approach, the study analyzes Qur'anic legal principles, Prophetic traditions, sira materials, usul al-fiqh concepts, and recent literature on ijtihad, maqasid, and legal adaptation. The findings show that Prophetic ijtihad functioned as guided legal reasoning: it remained anchored in revelation while using analogy, maslahah, consultation, gradualism, custom, and supervised delegation to the Companions. This pattern demonstrates that early Islamic law was neither rigid literalism nor unrestricted rationalism, but a disciplined method for connecting divine norms with concrete social needs. The article contributes a typology of Prophetic ijtihad and argues that it can inform contemporary Islamic legal thought through textual fidelity, public benefit, ethical purpose, and methodological accountability.